Pertanggungjawaban Nahkoda dalam Pengangkutan Laut Atas Kecelakaan Kapal di Indonesia - Jephyri Monang Siregar; Hulman Panjaitan; Wiwik Sri Widiarty (Syntax Idea)
This academic article aims to analyze the employment status certainty of seafarers from the perspective of Indonesian positive law. Seafarers are a unique group of workers as they work on ships that sail in international waters. In this context, the article documents and analyzes the legal framework governing the employment status of seafarers in Indonesia, as well as the common issues that arise in seafarer employment practices. The study examines the legal aspects that influence the employment status of seafarers, such as labor regulations, labor standards, and relevant international conventions. The article also highlights crucial issues, including workers' rights, terms of employment, wages, and social protection for seafarers. In this analysis, it will be considered how far Indonesian legal regulations provide employment status certainty for seafarers and how they are implemented in daily practice. The research also evaluates the challenges faced by seafarers in obtaining their rights and appropriate legal protection. The research findings indicate that the employment status certainty of seafarers under Indonesian positive law still requires attention and improvement. This article contributes to a deeper understanding of the legal framework governing seafarer employment and encourages improvements in regulations and the protection of seafarer employment rights in Indonesia.